Тамды районы қазақларының тилиндеги кәсиплик лексика - Қуттымуратова, Ы.А.; Кушкарбекова, М.Ү. (FAN va JAMIYAT, 2022)
The article provides a detailed study of the history of the Tamdi Kazakhs, as well as features in their language. The object of research is the peculiarities of the language of the Kazakhs of Tamdi district. The article reveals the invaluable heritage of Kazakh literature and rich oral tradition. It is also important that the Kazakh language is passed on to the next generation in its purest form.